2009
DOI: 10.1093/fampra/cmp070
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists and nurses as independent prescribers: exploring the patient's perspective

Abstract: The results indicate support for pharmacists and nurses as prescribers, which aid successful implementation. Further research may be needed to evaluate the level of understanding that the public has of NMP and their views of the service once NMP is more widely established. Stakeholders should be mindful that the public may be hesitant regarding the professionalism, quality and clinical governance standards of clinics in community pharmacies in particular.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
82
2
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(93 citation statements)
references
References 10 publications
2
82
2
6
Order By: Relevance
“…These studies have reported support and benefits from this role. 37,38,39,40 In Australia, Bessell et al also explored consumers' perspectives. These authors indicated that consumers were supportive of improved access to medications.…”
Section: A) Studies Exploring Pharmacists' Viewsmentioning
confidence: 99%
“…These studies have reported support and benefits from this role. 37,38,39,40 In Australia, Bessell et al also explored consumers' perspectives. These authors indicated that consumers were supportive of improved access to medications.…”
Section: A) Studies Exploring Pharmacists' Viewsmentioning
confidence: 99%
“…Stakeholders are generally satisfied with NMP [12-15] and report that it increases the accessibility and flexibility of services [16,17]. A number of benefits for NMPs themselves have also been reported including greater autonomy and increased job satisfaction, more time with patients and the ability to provide a complete episode of care, increased self-confidence, and time savings [18-21].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have explored the views of 18 patients who had experienced either pharmacist (eight patients) or nurse prescribing (10 patients). Patients acknowledged the drug knowledge of pharmacists but expressed concerns over potential privacy and space issues in community pharmacies even though none had experienced community pharmacy‐based prescribing services [8] …”
Section: Introductionmentioning
confidence: 99%